Why Bitcoin and Ethereum Differ in Transaction Costs: A Theory of Blockchain Fee Policies - Abdoulaye Ndiaye (CESifo GmbH, 2024)
Blockchains, the technology underlying cryptocurrencies, face large fluctuations in user demand and marginal costs. These fluctuations make effective fee policies necessary to manage transaction service allocation. This paper models the conflict between the blockchain designer and validators with monopoly power in choosing between price-setting and quantity-setting fee policies. The key determinants of the advantage of price-setting on blockchains are the validators' bargaining power, the elasticity of demand, the validators' uncertainty about demand, and the covariance of demand and marginal costs. My results help account for differences between the fee policy designs of Bitcoin and Ethereum, the leading blockchains, and have implications for how they can be improved.
Keywords: 330; blockchain; transaction costs; fee policies; Bitcoin; Ethereum; demand fluctuations; price elasticity